Preparing for Adolescence - James Clayton Dobson 1936- (U.S.A Regal Books, 1989)
Speaks to adolescents about such topics as drug abuse, sex, family conflict, friendship, love, and conformity.
Keywords: Philosophy and Psychology (3GdadSaI hYde GdfaSs; Adolescence -- Juvenile literature; Teenagers -- Conduct of life; Teenagers -- General -- Religious life